2019
DOI: 10.1371/journal.pone.0222936
|View full text |Cite
|
Sign up to set email alerts
|

DNA analysis of Castanea sativa (sweet chestnut) in Britain and Ireland: Elucidating European origins and genepool diversity

Abstract: Castanea sativa is classified as non-indigenous in Britain and Ireland. It was long held that it was first introduced into Britain by the Romans, until a recent study found no corroborative evidence of its growing here before c. AD 650. This paper presents new data on the genetic diversity of C. sativa in Britain and Ireland and potential ancestral sources in continental Europe. Microsatellite markers and analytical methods tested in previous European studies were used to genotype over 600 C. sativa trees and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…So far, population genetics have already been used to answer a broad range of questions related to pathogen biology (including parasitology). Examples of this include the elucidation of clonality in pathogens (e.g., Hill et al, 1995; Morehouse et al, 2003) and understanding the spatial structure and diversity of a pathogen in a geographical range (e.g., Anderson et al, 2000; Mekonnen et al, 2020) which can further be used to identify the source population of a pathogen's introduction (e.g., Jarman et al, 2019). These types of studies investigate patterns over long (evolutionary) time frames, which are an important part of the framework for understanding wildlife diseases (e.g., Vander Wal et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…So far, population genetics have already been used to answer a broad range of questions related to pathogen biology (including parasitology). Examples of this include the elucidation of clonality in pathogens (e.g., Hill et al, 1995; Morehouse et al, 2003) and understanding the spatial structure and diversity of a pathogen in a geographical range (e.g., Anderson et al, 2000; Mekonnen et al, 2020) which can further be used to identify the source population of a pathogen's introduction (e.g., Jarman et al, 2019). These types of studies investigate patterns over long (evolutionary) time frames, which are an important part of the framework for understanding wildlife diseases (e.g., Vander Wal et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Anderson et al, 2000; Mekonnen et al, 2020) which can further be used to identify the source population of a pathogen’s introduction (e.g. Jarman et al, 2019). These types of studies investigate patterns of large (evolutionary) time frames, which are a valid and important part of the framework to understanding wildlife diseases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it was reported that the information included in the analyses of a number of microsatellites ranging from 16 to 24 is enough for a robust estimation of distances among European chestnuts [ 23 , 41 , 42 ] and that, in allogamous species, the variability monitored by a microsatellite corresponds to the variability that can be monitored by seven to 11 SNPs [ 43 ]. In the more recent literature, the use of microsatellite molecular markers combined with agronomic and morphological observations was very useful for studying stress adaptation and the genetic origin of the European chestnut populations [ 20 , 21 , 42 , 44 ]. The provided widening of the available molecular tools will open up new horizons for these applications.…”
Section: Discussionmentioning
confidence: 99%
“…These markers are efficient, reliable and were widely used for population studies and cultivar genotyping. Recently, they have been used for characterizing Iberian and British populations and, combined with morphological observations, they allowed to come to important practical conclusions about natural populations’ biodiversity [ 20 , 21 ]. Nonetheless, they require a workflow that is not compatible with cost effective and easy-to-use applications as it includes a thorough DNA purification, amplification in presence of fluorescent-labeled primers, capillary electrophoresis, as well as complex data elaboration.…”
Section: Introductionmentioning
confidence: 99%